Millennium Development Goals (MDG) Gap Task Force Report 2015 - United Nations (United Nations, 2015)
The present report was prepared by the MDG Gap Task Force, which was created by the Secretary-General of the United Nations to improve the monitoring of MDG 8 by leveraging inter-agency coordination. More than 30 United Nations entities and other organizations are represented in the Task Force, including the World Bank and the International Monetary Fund, as well as the Organization for Economic Cooperation and Development and the World Trade Organization. The Department of Economic and Social Affairs of the United Nations Secretariat (UN/DESA) and the United Nations Development Programme (UNDP) acted as lead agencies in organizing the work of the Task Force.